2011
DOI: 10.1111/j.1740-8261.2011.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Computed Tomography in Feline Patients Without Use of Chemical Restraint

Abstract: Computed tomography (CT) and thoracic radiography were performed in nonsedated, nonanesthetized, cats with thoracic disease. The final diagnosis was obtained with echocardiography, cytology, histopathology, necropsy, or response to therapy. For CT imaging, cats were in a positioning device using a 16 multislice helical CT system. Fifty-four cats had CT imaging of which 50 had thoracic radiography. The most common diagnoses were lung neoplasia, lower airway disease, and cardiomyopathy (nine each). Other disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 18 publications
5
50
1
2
Order By: Relevance
“…This is consistent with reports in small animals describing the use of MDCT in awake or sedated animal for the acquisition of pelvic CTs for trauma evaluation in dogs, the abdomen in dogs with acute abdominal signs, and studies of the cat respiratory tract for assessment of upper airway obstruction (1113, 15). Although calves with respiratory disease commonly have tachypnea and cough as well as other signs of respiratory compromise, the plane of sedation provided by the sedation protocol described herein allowed acquisition of CT images with a generally mild degree of respiratory motion, which did not preclude evaluation of the bronchial tree or pulmonary vasculature or parenchyma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with reports in small animals describing the use of MDCT in awake or sedated animal for the acquisition of pelvic CTs for trauma evaluation in dogs, the abdomen in dogs with acute abdominal signs, and studies of the cat respiratory tract for assessment of upper airway obstruction (1113, 15). Although calves with respiratory disease commonly have tachypnea and cough as well as other signs of respiratory compromise, the plane of sedation provided by the sedation protocol described herein allowed acquisition of CT images with a generally mild degree of respiratory motion, which did not preclude evaluation of the bronchial tree or pulmonary vasculature or parenchyma.…”
Section: Discussionsupporting
confidence: 90%
“…However, calves with severe respiratory impairment due to pneumonia often have an increased anesthetic risk. Although CT scanning protocols have been described for awake and sedated patients including for normal cats and cats with upper airway obstruction and intrathoracic disease, dogs with acute abdominal signs, and dogs with traumatic pelvic fractures, as well as healthy sedated foals neither has been evaluated in calves to date (1115). …”
Section: Introductionmentioning
confidence: 99%
“…A specially designed restraint device has greatly facilitated CT imaging in awake or minimally sedated cats and small dogs. 6,27,28 For safety and practical reasons, larger animals, particularly neonatal foals, cannot undergo imaging when awake; however, the use of short-term IV sedation may provide a safe alternative to anesthesia in this population of animals.…”
Section: Humentioning
confidence: 99%
“…[1][2][3][4][5] In veterinary medicine, radiography remains the standard method for imaging the lungs, 6,7 although the use of CT for the diagnosis of thoracic disease in dogs and cats has been well described. [6][7][8] In sick equine neonates, respiratory disease is a clinically important factor contributing to illness and death, with immaturity of pulmonary and systemic immunity and concurrent systemic disease such as sepsis predisposing foals to pulmonary disease. [9][10][11][12][13] The diagnosis and characterization of respiratory disease in hospitalized foals largely rely on radiographic analysis.…”
mentioning
confidence: 99%
“…14,15 These studies employed a novel device (e.g., VetMouseTrap TM ) that allowed imaging of alert cats with minimal motion artifact. 14,15 In both studies, diagnostic quality CT images were obtained. 14,15 A recent CT study evaluating awake swans found similar results.…”
mentioning
confidence: 99%